19th Acta Physiologica international symposium ‘WNT Signaling in Physiology and Disease’– a long way from developmental biology to physiology - Schulte, G.; Bryja, Vitslav; Schambony, Alexandra (Acta Physiologica, 2012)
In 1996, a series of Acta Physiologica international symposia sponsored by the Scandinavian Physiological Society was initiated. This issue of Acta Physiologica contains 10 review articles from participants at the 19th Acta Physiologica International Symposium

A homologue of cysteine-rich secretory proteins induces premature degradation of vitelline envelopes and hatching of Xenopus laevis embryos. - Schambony, Alexandra; Hefele, Jörg; Gentzel, Marc; Wilm, Matthias; Wedlich, Doris (Mechanisms of Development, 2003)
We cloned Xenopus laevis CRISP, XCRISP, a homologue of the mammalian family of cysteine-rich secretory proteins (CRISPs), which has been previously identified as a Wnt3a/noggin responsive gene in an expression screen [Mech. Dev. 87 (1999) 21]. We detected XCRISP expression exclusively in the hatching gland. XCRISP enters the secretory pathway and accumulates on the surface of presumptive hatching gland cells. Overexpression studies of XCRISP and XCRISP-mutants show that XCRISP induces premature hatching of embryos preceded by degradation of the vitelline envelope. A deletion mutant that lacks a 35 amino acid domain even accelerates hatching, while further deletion of the carboxy-terminus reverses these effects. From our studies, we conclude that XCRISP is sufficient to induce degradation of vitelline envelopes and that this activity maps to the most C-terminal amino acids, while the adjacent domain regulates XCRISP activity.

Amer2 protein interacts with EB1 protein and adenomatous polyposis coli (APC) and controls microtubule stability and cell migration. - Pfister, Astrid; Hadjihannas, Michel; Roehrig, Waldemar; Schambony, Alexandra; Behrens, Jürgen (Journal of Biological Chemistry, 2012)
EB1 is key factor in the organization of the microtubule cytoskeleton by binding to the plus-ends of microtubules and serving as a platform for a number of interacting proteins (termed +TIPs) that control microtubule dynamics. Together with its direct binding partner adenomatous polyposis coli (APC), EB1 can stabilize microtubules. Here, we show that Amer2 (APC membrane recruitment 2), a previously identified membrane-associated APC-binding protein, is a direct interaction partner of EB1 and acts as regulator of microtubule stability together with EB1. Amer2 binds to EB1 via specific (S/T)xIP motifs and recruits it to the plasma membrane. Coexpression of Amer2 and EB1 generates stabilized microtubules at the plasma membrane, whereas knockdown of Amer2 leads to destabilization of microtubules. Knockdown of Amer2, APC, or EB1 reduces cell migration, and morpholino-mediated down-regulation of Xenopus Amer2 blocks convergent extension cell movements, suggesting that the Amer2-EB1-APC complex regulates cell migration by altering microtubule stability.

Amer2 protein is a novel negative regulator of Wnt/β-catenin signaling involved in neuroectodermal patterning. - Pfister, Astrid; Tanneberger, Kristina; Schambony, Alexandra; Behrens, Jürgen (Journal of Biological Chemistry, 2012)
Wnt/β-catenin signaling is negatively controlled by the adenomatous polyposis coli (APC) tumor suppressor, which induces proteasomal degradation of β-catenin as part of the β-catenin destruction complex. Amer2 (APC membrane recruitment 2; FAM123A) is a direct interaction partner of APC, related to the tumor suppressor Amer1/WTX, but its function in Wnt signaling is not known. Here, we show that Amer2 recruits APC to the plasma membrane by binding to phosphatidylinositol 4,5-bisphosphate lipids via lysine-rich motifs and that APC links β-catenin and the destruction complex components axin and conductin to Amer2. Knockdown of Amer2 increased Wnt target gene expression and reporter activity in cell lines, and overexpression reduced reporter activity, which required membrane association of Amer2. In Xenopus embryos, Amer2 is expressed mainly in the dorsal neuroectoderm and neural tissues. Down-regulation of Amer2 by specific morpholino oligonucleotides altered neuroectodermal patterning, which could be rescued by expression of a dominant-negative mutant of Lef1 that interferes with β-catenin-dependent transcription. Our data characterize Amer2 for the first time as a negative regulator of Wnt signaling both in cell lines and in vivo and define Amer proteins as a novel family of Wnt pathway regulators.

A paintbrush for delivery of nanoparticles and molecules to live cells with precise spatiotemporal control - Holler, Cornelia; Taylor, Richard William; Schambony, Alexandra; Möckl, Leonhard; Sandoghdar, Vahid (Nature methods, 2024)
Delivery of very small amounts of reagents to the near-field of cells with micrometer spatial precision and millisecond time resolution is currently out of reach. Here we present μkiss as a micropipette-based scheme for brushing a layer of small molecules and nanoparticles onto the live cell membrane from a subfemtoliter confined volume of a perfusion flow. We characterize our system through both experiments and modeling, and find excellent agreement. We demonstrate several applications that benefit from a controlled brush delivery, such as a direct means to quantify local and long-range membrane mobility and organization as well as dynamical probing of intercellular force signaling.
CRIS-Team Scopus Importer:2024-02-23

Beta-arrestin is a necessary component of Wnt/beta-catenin signaling in vitro and in vivo. - Bryja, Vitezslav; Gradl, Dietmar; Schambony, Alexandra; Arenas, Ernest; Schulte, Gunnar (Proceedings of the National Academy of Sciences of the United States of America, 2007)
The Wnt/beta-catenin signaling pathway is crucial for proper embryonic development and tissue homeostasis. The phosphoprotein dishevelled (Dvl) is an integral part of Wnt signaling and has recently been shown to interact with the multifunctional scaffolding protein beta-arrestin. Using Dvl deletion constructs, we found that beta-arrestin binds a region N-terminal of the PDZ domain of Dvl, which contains casein kinase 1 (CK1) phosphorylation sites. Inhibition of Wnt signaling by CK1 inhibitors reduced the binding of beta-arrestin to Dvl. Moreover, mouse embryonic fibroblasts lacking beta-arrestins were able to phosphorylate LRP6 in response to Wnt-3a but decreased the activation of Dvl and blocked beta-catenin signaling. In addition, we found that beta-arrestin can bind axin and forms a trimeric complex with axin and Dvl. Furthermore, treatment of Xenopus laevis embryos with beta-arrestin morpholinos reduced the activation of endogenous beta-catenin, decreased the expression of the beta-catenin target gene, Xnr3, and blocked axis duplication induced by X-Wnt-8, CK1epsilon, or DshDeltaDEP, but not by beta-catenin. Thus, our results identify beta-arrestin as a necessary component for Wnt/beta-catenin signaling, linking Dvl and axin, and open a vast array of signaling avenues and possibilities for cross-talk with other beta-arrestin-dependent signaling pathways.

Biochemical and conformational characterisation of HSP-3, a stallion seminal plasma protein of the cysteine-rich secretory protein (CRISP) family. - Schambony, Alexandra; et al. (FEBS letters, 1997)
HSP-3 is a member of the cysteine-rich secretory protein (CRISP) family from stallion seminal plasma. We report a large-scale purification protocol for native HSP-3. This protein is a non-glycosylated polypeptide chain with a pI of 8-9 and an isotope-averaged molecular mass of 24987 +/- 3 Da. The molecular mass of HSP-3, determined by equilibrium sedimentation, is 26 kDa, showing that the protein exists in solution as a monomer. The concentration of HSP-3 in the seminal plasma of different stallions ranged from 0.3 to 1.3 mg/ml. On average, 0.9-9 million HSP-3 molecules/cell coat the postacrosomal and mid-piece regions of an ejaculated, washed stallion spermatozoon, suggesting a role in sperm physiology. Conformational characterisation of purified HSP-3 was assessed by combination of circular dichroism and Fourier-transform infrared spectroscopies and differential scanning microcalorimetry. Based on secondary structure assignment, HSP-3 may belong to the alpha+beta class of proteins. Thermal denaturation of HSP-3 is irreversible and follows a non-two state transition characterised by a Tm of 64 degrees C, an enthalpy change of 75 kcal/mol, and a van 't Hoff enthalpy of 184 kcal/mol. Analysis of the spectroscopic and calorimetric data indicates the occurrence of aggregation of denatured HSP-3 molecules and suggests the monomer as the cooperative unfolding unit.

Cell migration under control of Wnt‐signaling in the vertebrate embryo - Schambony, Alexandra; et al. (Advances in Developmental Biology, 2007)
During embryonic development, cell fate specification and morphogenetic movements are tightly controlled by a network of signaling cascades. Among these, Wnt-signaling historically has predominantly been associated with cell fate decisions, however, during the

Cross-regulation of Wnt signaling and cell adhesion. - Schambony, Alexandra; Kunz, Martin; Gradl, Dietmar (Differentiation, 2004)
The complex cross-regulation between Wnt signaling, cell-cell adhesion, and cell-matrix adhesion has revealed a number of regulatory components important in development and cancer progression. In the following, we would like to highlight and summarize some of the steps where pathways converge or diverge in regulating Wnt activity, matrix-induced pathways, and cell adhesion. We would like to focus on the involvement of heparan sulfate proteoglycan-rich proteins (HSPGs), integrin-mediated outside-in signaling, and cadherin-mediated cell-cell adhesion on Wnt pathways and the transcriptional regulation of extracellular matrix components and cell adhesion molecules by Wnt signaling.

Differential requirement of bone morphogenetic protein receptors Ia (ALK3) and Ib (ALK6) in early embryonic patterning and neural crest development. - Schille, Carolin; Heller, Jens; Schambony, Alexandra (Bmc Developmental Biology, 2016)
BACKGROUND:Bone morphogenetic proteins regulate multiple processes in embryonic development, including early dorso-ventral patterning and neural crest development. BMPs activate heteromeric receptor complexes consisting of type I and type II receptor-serine/threonine kinases. BMP receptors Ia and Ib, also known as ALK3 and ALK6 respectively, are the most common type I receptors that likely mediate most BMP signaling events. Since early expression patterns and functions in Xenopus laevis development have not been described, we have addressed these questions in the present study.RESULTS:Here we have analyzed the temporal and spatial expression patterns of ALK3 and ALK6; we have also carried out loss-of-function studies to define the function of these receptors in early Xenopus development. We detected both redundant and non-redundant roles of ALK3 and ALK6 in dorso-ventral patterning. From late gastrula stages onwards, their expression patterns diverged, which correlated with a specific, non-redundant requirement of ALK6 in post-gastrula neural crest cells. ALK6 was essential for induction of neural crest cell fate and further development of the neural crest and its derivatives.CONCLUSIONS:ALK3 and ALK6 both contribute to the gene regulatory network that regulates dorso-ventral patterning; they play partially overlapping and partially non-redundant roles in this process. ALK3 and ALK6 are independently required for the spatially restricted activation of BMP signaling and msx2 upregulation at the neural plate border, whereas in post-gastrula development ALK6 exerts a highly specific, conserved function in neural crest development.

Dishevelled-3 conformation dynamics analyzed by FRET-based biosensors reveals a key role of casein kinase 1 - Harnos, Jakub; Canizal, Maria Consuelo Alonso; Jurasek, Miroslav; Kumar, Jitender; Holler, Cornelia; Schambony, Alexandra; Hanakova, Katerina; Bernatik, Ondrej; Zdrahal, Zbynek; Gomoryova, Kristina; Gybel, Tomas; Radaszkiewicz, Tomasz Witold; et al. (Nature Communications, 2019)
Dishevelled (DVL) is the key component of the Wnt signaling pathway. Currently, DVL conformational dynamics under native conditions is unknown. To overcome this limitation, we develop the Fluorescein Arsenical Hairpin Binder- (FlAsH-) based FRET in vivo approach to study DVL conformation in living cells. Using this single-cell FRET approach, we demonstrate that (i) Wnt ligands induce open DVL conformation, (ii) DVL variants that are predominantly open, show more even subcellular localization and more efficient membrane recruitment by Frizzled (FZD) and (iii) Casein kinase 1 ɛ (CK1ɛ) has a key regulatory function in DVL conformational dynamics. In silico modeling and in vitro biophysical methods explain how CK1ɛ-specific phosphorylation events control DVL conformations via modulation of the PDZ domain and its interaction with DVL C-terminus. In summary, our study describes an experimental tool for DVL conformational sampling in living cells and elucidates the essential regulatory role of CK1ɛ in DVL conformational dynamics.
CRIS-Team Scopus Importer:2019-05-02

Dishevelled Paralogs in Vertebrate Development: Redundant or Distinct? - Gentzel, Marc; Schambony, Alexandra (Frontiers in Cell and Developmental Biology, 2017)
Dishevelled (DVL) proteins are highly conserved in the animal kingdom and are important key players in β-Catenin-dependent and -independent Wnt signaling pathways. Vertebrate genomes typically comprise three DVL genes, DVL1, DVL2, and DVL3. Expression patterns and developmental functions of the three vertebrate DVL proteins however, are only partially redundant in any given species. Moreover, expression and function of DVL isoforms have diverged between different vertebrate species. All DVL proteins share basic functionality in Wnt signal transduction. Additional, paralog-specific interactions and functions combined with context-dependent availability of DVL isoforms may play a central role in defining Wnt signaling specificity and add selectivity toward distinct downstream pathways. In this review, we recapitulate briefly cellular functions of DVL paralogs, their role in vertebrate embryonic development and congenital disease.

Distinct functionality of dishevelled isoforms on Ca2+/calmodulin-dependent protein kinase 2 (CamKII) in Xenopus gastrulation. - Gentzel, Marc; Schille, Carolin; Rauschenberger, Verena; Schambony, Alexandra (Molecular Biology of the Cell, 2015)
Wnt ligands trigger the activation of a variety of β-catenin-dependent and β-catenin-independent intracellular signaling cascades. Despite the variations in intracellular signaling, Wnt pathways share the effector proteins frizzled, dishevelled, and β-arrestin. It is unclear how the specific activation of individual branches and the integration of multiple signals are achieved. We hypothesized that the composition of dishevelled-β-arrestin protein complexes contributes to signal specificity and identified CamKII as an interaction partner of the dishevelled-β-arrestin protein complex by quantitative functional proteomics. Specifically, we found that CamKII isoforms interact differentially with the three vertebrate dishevelled proteins. Dvl1 is required for the activation of CamKII and PKC in the Wnt/Ca(2+) pathway. However, CamKII interacts with Dvl2 but not with Dvl1, and Dvl2 is necessary to mediate CamKII function downstream of Dvl1 in convergent extension movements in Xenopus gastrulation. Our findings indicate that the different Dvl proteins and the composition of dishevelled-β-arrestin protein complexes contribute to the specific activation of individual branches of Wnt signaling.

EFhd2/Swiprosin-1 is a common genetic determinator for sensation-seeking/low anxiety and alcohol addiction - Mielenz, Dirk; Reichel, Martin; Jia, T.; Quinlan, E. B.; Stöckl, Thomas; Mettang, M.; Zilske, Daniel; Kirmizi Alsan, Elif; Schoenberger, P.; Praetner, M.; Huber, Sabine; Amato, Davide; et al. (Molecular Psychiatry, 2017)
In many societies, the majority of adults regularly consume alcohol. However, only a small proportion develops alcohol addiction. Individuals at risk often show a high sensation-seeking/low-anxiety behavioural phenotype. Here we asked which role EF hand domain containing 2 (EFhd2; Swiprosin-1) plays in the control of alcohol addiction-associated behaviours. EFhd2 knockout (KO) mice drink more alcohol than controls and spontaneously escalate their consumption. This coincided with a sensation-seeking and low-anxiety phenotype. A reversal of the behavioural phenotype with β-carboline, an anxiogenic inverse benzodiazepine receptor agonist, normalized alcohol preference in EFhd2 KO mice, demonstrating an EFhd2-driven relationship between personality traits and alcohol preference. These findings were confirmed in a human sample where we observed a positive association of the EFhd2 single-nucleotide polymorphism rs112146896 with lifetime drinking and a negative association with anxiety in healthy adolescents. The lack of EFhd2 reduced extracellular dopamine levels in the brain, but enhanced responses to alcohol. In confirmation, gene expression analysis revealed reduced tyrosine hydroxylase expression and the regulation of genes involved in cortex development, Eomes and Pax6, in EFhd2 KO cortices. These findings were corroborated in Xenopus tadpoles by EFhd2 knockdown. Magnetic resonance imaging (MRI) in mice showed that a lack of EFhd2 reduces cortical volume in adults. Moreover, human MRI confirmed the negative association between lifetime alcohol drinking and superior frontal gyrus volume. We propose that EFhd2 is a conserved resilience factor against alcohol consumption and its escalation, working through Pax6/Eomes. Reduced EFhd2 function induces high-risk personality traits of sensation-seeking/low anxiety associated with enhanced alcohol consumption, which may be related to cortex function.
EVALuna2:4036

EFHD2/SWIPROSIN-1 IS A CONSERVED RESILIENCE FACTOR AGAINST ALCOHOL DRINKING ESCALATION - Müller, Christian P.; Reichel, Martin; Jia, T.; Quinlan, E. B.; Schambony, Alexandra; Bäuerle, Tobias; Eulenburg, Volker; Lourdusamy, A.; Schumann, G.; Mielenz, Dirk (2018)
EVALuna2:35243

Equine CRISP-3: primary structure and expression in the male genital tract. - Schambony, Alexandra; et al. (Biochimica et Biophysica Acta (BBA) - Protein Structure and Molecular Enzymology, 1998)
Although originally described in the male rodent genital tract, cysteine-rich secretory proteins (CRISPs) are expressed in a variety of mammalian tissue and cell types. The proteins of the male genital tract have been observed associated to spermatozoa and are believed to play a role in mammalian fertilization. Here we describe the identification and primary structure of the first equine member of the CRISP family. Equine CRISP-3 is transcribed and expressed in the stallion salivary gland, in the ampulla and the seminal vesicle. It displays all 16 conserved cysteine residues and shows 82% homology to human and 78% to guinea pig CRISP-2 (AA1, TPX 1) and 77% to human CRISP-3. In contrast to other mammalia, in the horse CRISP-3 is synthesized in great amounts in the accessory sexual glands, ampulla and seminal vesicle, thus allowing the isolation of equine CRISP-3 in amounts suitable for biochemical, physiological and structural studies from stallion seminal plasma.

Erratum to: Gap junction protein Connexin-43 is a direct transcriptional regulator of N-cadherin in vivo (Nature Communications, (2018), 9, 1, (3846), 10.1038/s41467-018-06368-x) - Kotini, Maria; Barriga, Elias H.; Leslie, Jonathan; Gentzel, Marc; Rauschenberger, Verena; Schambony, Alexandra; Mayor, Roberto (Nature Communications, 2018)
Correction to: Nature Communications (2018); https://doi.org/10.1038/s41467-018-06368-x, published online 21 September 2018 The original version of this Article contained an error in the spelling of the author Alexandra Schambony, which was incorrectly given as Alexandra Schambon. This has now been corrected in both the PDF and HTML versions of the Article.
CRIS-Team Scopus Importer:2022-08-05

Expression of CRISP proteins in the male equine genital tract. - Schambony, Alexandra; et al. (Journal of reproduction and fertility. Supplement, 1998)
Cysteine rich secretory proteins (CRISPs) have been detected immunochemically in the equine male genital tract. CRISPs are secretory products of the epididymis, the ampulla and the seminal vesicle. A particular feature of the horse is the abundance of CRISPs in seminal plasma. CRISPs can also be detected in extracts of testicular, epididymal and ejaculated spermatozoa in increasing amounts. Unlike other seminal plasma proteins, they cannot be removed completely from spermatozoa by high salt treatment. The remaining CRISP antigens are localized on the midpiece, and the postacrosomal and equatorial region of the sperm head. Tissue distribution and localization of CRISPs on equine spermatozoa point to a role of these proteins in epididymal sperm maturation and equine reproduction.
Keywords: get pdf

Functional analysis of dishevelled-3 phosphorylation identifies distinct mechanisms driven by casein kinase 1ϵ and frizzled5. - Bernatik, Ondrej; Sedova, Katerina; Schille, Carolin; Ganji, Ranjani Sri; Cervenka, Igor; Trantirek, Lukas; Schambony, Alexandra; Zdrahal, Zbynek; Bryja, Vitezslav (Journal of Biological Chemistry, 2014)
Dishevelled-3 (Dvl3), a key component of the Wnt signaling pathways, acts downstream of Frizzled (Fzd) receptors and gets heavily phosphorylated in response to pathway activation by Wnt ligands. Casein kinase 1ε (CK1ε) was identified as the major kinase responsible for Wnt-induced Dvl3 phosphorylation. Currently it is not clear which Dvl residues are phosphorylatedandwhatis theconsequenceof individualphosphorylation events. In the present study we employed mass spectrometry to analyze in a comprehensive way the phosphorylation of human Dvl3 induced by CK1ε. Our analysis revealed >50 phosphorylation sites on Dvl3; only a minority of these sites was found dynamically induced after co-expression of CK1ε, and surprisingly, phosphorylation of one cluster of modified residues was down-regulated. Dynamically phosphorylated sites were analyzed functionally. Mutations within PDZ domain (S280A and S311A) reduced the ability of Dvl3 to activate TCF/ LEF (T-cell factor/lymphoid enhancer factor)-driven transcription and induce secondary axis in Xenopus embryos. In contrast, mutations of clustered Ser/Thr in the Dvl3 C terminus prevented ability of CK1ε to induce electrophoretic mobility shift of Dvl3 and its even subcellular localization. Surprisingly, mobility shift and subcellular localization changes induced by Fzd5, a Wnt receptor, were in all these mutants indistinguishable from wild type Dvl3. In summary, our data on the molecular level (i) support previous the assumption that CK1ε acts via phosphorylation of distinct residues as the activator as well as the shut-off signal of Wnt/β-catenin signaling and (ii) suggest that CK1ε acts on Dvl via different mechanism than Fzd5. © 2014 by The American Society for Biochemistry and Molecular Biology, Inc.

High-Precision Protein-Tracking With Interferometric Scattering Microscopy - Taylor, Richard W.; Holler, Cornelia; Mahmoodabadi, Reza Gholami; Küppers, Michelle; Mirzaalian Dastjerdi, Houman; Zaburdaev, Vasily; Schambony, Alexandra; Sandoghdar, Vahid (Frontiers in Cell and Developmental Biology, 2020)
The mobility of proteins and lipids within the cell, sculpted oftentimes by the organization of the membrane, reveals a great wealth of information on the function and interaction of these molecules as well as the membrane itself. Single particle tracking has proven to be a vital tool to study the mobility of individual molecules and unravel details of their behavior. Interferometric scattering (iSCAT) microscopy is an emerging technique well-suited for visualizing the diffusion of gold nanoparticle-labeled membrane proteins to a spatial and temporal resolution beyond the means of traditional fluorescent labels. We discuss the applicability of interferometric single particle tracking (iSPT) microscopy to investigate the minutia in the motion of a protein through measurements visualizing the mobility of the epidermal growth factor receptor in various biological scenarios on the live cell.
CRIS-Team Scopus Importer:2020-11-27
Keywords: epidermal growth factor receptor; interferometric scattering microscopy; iSCAT; iSPT; live cell imaging; membrane organization; single particle tracking

High-resolution, three-dimensional investigation of protein diffusion and trafficking in the live HeLa cell via interferometrie scattering microscopy (iSCAT) - Taylor, Richard; Mahmoodabadi, Reza Gholami; Schambony, Alexandra; Sandoghdar, Vahid (2019 Conference on Lasers and Electro-Optics Europe and European Quantum Electronics Conference, CLEO/Europe-EQEC 2019, 2019)
Transmembrane proteins exhibit a wide variety of mobility in live cells, including diffusion in the plasma membrane and directed transport into the cell via endocytosis. Although a great deal has been uncovered about the biochemistry underlying these processes, their real-time visualisation in situ with the necessary nanoscopic resolution remains a daunting experimental challenge. Conventional microscopies rely on fluorescent labelling to monitor diffusion of such proteins within live cells. The resolution in both space and time by which one can successfully determine the position of the protein is curtailed by the finite and limited emission rate of the fluorophore.
CRIS-Team Scopus Importer:2019-11-15

hmmr mediates anterior neural tube closure and morphogenesis in the frog Xenopus - Prager, Angela; Hagenlocher, Cathrin; Ott, Tim; Schambony, Alexandra; Feistel, Kerstin (Developmental Biology, 2017)
Development of the central nervous system requires orchestration of morphogenetic processes which drive elevation and apposition of the neural folds and their fusion into a neural tube. The newly formed tube gives rise to the brain in anterior regions and continues to develop into the spinal cord posteriorly. Conspicuous differences between the anterior and posterior neural tube become visible already during neural tube closure (NTC). Planar cell polarity (PCP)-mediated convergent extension (CE) movements are restricted to the posterior neural plate, i.e. hindbrain and spinal cord, where they propagate neural fold apposition. The lack of CE in the anterior neural plate correlates with a much slower mode of neural fold apposition anteriorly. The morphogenetic processes driving anterior NTC have not been addressed in detail. Here, we report a novel role for the breast cancer susceptibility gene and microtubule (MT) binding protein Hmmr (Hyaluronan-mediated motility receptor, RHAMM) in anterior neurulation and forebrain development in Xenopus laevis. Loss of hmmr function resulted in a lack of telencephalic hemisphere separation, arising from defective roof plate formation, which in turn was caused by impaired neural tissue narrowing. hmmr regulated polarization of neural cells, a function which was dependent on the MT binding domains. hmmr cooperated with the core PCP component vangl2 in regulating cell polarity and neural morphogenesis. Disrupted cell polarization and elongation in hmmr and vangl2 morphants prevented radial intercalation (RI), a cell behavior essential for neural morphogenesis. Our results pinpoint a novel role of hmmr in anterior neural development and support the notion that RI is a major driving force for anterior neurulation and forebrain morphogenesis.
CRIS-Team Scopus Importer:2022-08-05
Keywords: Convergent extension; hmmr; Neural tube closure; Radial intercalation; Rhamm; Xenopus laevis

HOX genes regulate Rac1 activity in hematopoietic cells through control of Vav2 expression - Breitinger, Constanze; Mäthner, Emanuel; Garcia-Cuellar, Maria-Paz; Schambony, Alexandra; Fischer, K. D.; Schilling, K.; Slany, Robert (Leukemia, 2013)

Interferometric scattering microscopy reveals microsecond nanoscopic protein motion on a live cell membrane - Taylor, Richard W.; Mahmoodabadi, Reza Gholami; Rauschenberger, Verena; Gießl, Andreas; Schambony, Alexandra; Sandoghdar, Vahid (Nature Photonics, 2019)
Many of the biological functions of a cell are dictated by the intricate motion of proteins within its membrane over a spatial range of nanometres to tens of micrometres and time intervals of microseconds to minutes. This rich parameter space is not accessible by fluorescence microscopy, but it is within reach of interferometric scattering (iSCAT) particle tracking. However, as iSCAT is sensitive even to single unlabelled proteins, it is often accompanied by a large speckle-like background, which poses a substantial challenge for its application to cellular imaging. Here, we employ a new image processing approach to overcome this difficulty and demonstrate tracking of transmembrane epidermal growth factor receptors with nanometre precision in all three dimensions at up to microsecond speeds and for durations of tens of minutes. We provide examples of nanoscale motion and confinement in ubiquitous processes such as diffusion in the plasma membrane, transport on filopodia and rotational motion during endocytosis.
CRIS-Team Scopus Importer:2019-05-02

Isothiocyanate-functionalized RGD peptides for tailoring cell-adhesive surface patterns. - Kalinina, Sviatlana; Gliemann, Hartmut; Lopez-Garcia, Monica; Petershans, Andre; Auernheimer, Joerg; Schimmel, Thomas; Bruns, Michael; Schambony, Alexandra; Kessler, Horst; Wedlich, Doris (Biomaterials, 2008)
With the advances made in surface patterning by micro- and nanotechnology, alternative methods to immobilize biomolecules for different purposes are highly desired. RGD peptides are commonly used to create cell-attractive surfaces for cell-biological and also medical applications. We have developed a fast, one-step method to bind RGD peptides covalently to surfaces by thiourea formation, which can be applied to structured and unstructured materials. RGD peptides were fused to an isothiocyanate anchor during synthesis and directly immobilized on amino-terminated surfaces. The spreading behavior of fibroblasts and the formation of focal contacts served to prove the applicability of the coupling method. Two different linear peptides and one cyclic peptide were compared. All the peptides induced spreading behavior and the formation of focal contacts in murine fibroblasts. Adhesion was specific as cells neither recognized the corresponding negative control peptides nor spread in the presence of soluble H-RGDS-OH peptide. We successfully applied our coupling method to functionalize surface patterns created by microcontact printing (microCP) and chemical etching. Cells recognize areas selectively coated with RGD-containing peptides, proliferate and maintain this preference during long-term cultivation. Our method significantly facilitates surface modification with any kind of peptide - even for the preparation of peptide-functionalized small surface areas.

Label-free live-cell imaging with interferometric scattering microscopy: Confocal imaging and high-speed 3D single particle tracking - Küppers, Michelle; Kashkanova, Anna; Lühr, Jennifer; Albrecht, David; Schambony, Alexandra; Sandoghdar, Vahid (Optics InfoBase Conference Papers, 2020)
The combination of interferometric scattering microscopy (iSCAT) in wide-field and confocal detection reveals new prospects for the label-free visualization of subcellular processes and tracking of nanoscopic matter such as viruses, vesicles and lipid droplets.
CRIS-Team Scopus Importer:2020-10-02

Lipid Dynamics in Membranes Slowed Down by Transmembrane Proteins - Ebersberger, Lisa; Schindler, Torben; Kirsch, Sonja; Pluhackova, Kristyna; Schambony, Alexandra; Seydel, Tilo; Böckmann, Rainer; Unruh, Tobias (Frontiers in Cell and Developmental Biology, 2020)
Lipids and proteins, as essential components of biological cell membranes, exhibit a significant degree of freedom for different kinds of motions including lateral long-range mobility. Due to their interactions, they not only preserve the cellular membrane but also contribute to many important cellular functions as e.g., signal transport or molecular exchange of the cell with its surrounding. Many of these processes take place on a short time (up to some nanoseconds) and length scale (up to some nanometers) which is perfectly accessible by quasielastic neutron scattering (QENS) experiments and molecular dynamics (MD) simulations. In order to probe the influence of a peptide, a transmembrane sequence of the transferrin receptor (TFRC) protein, on the dynamics of 1,2-dimyristoyl-sn-glycero-3-phosphocholine (DMPC) large unilamellar vesicles (LUVs) on a nanosecond time scale, high-resolution QENS experiments and complementary MD simulations have been utilized. By using different scattering contrasts in the experiment (chain-deuterated lipids and protonated lipids, respectively), a model could be developed which allows to examine the lipid and peptide dynamics separately. The experimental results revealed a restricted lipid lateral mobility in the presence of the TFRC transmembrane peptides. Also the apparent self-diffusion coefficient of the lateral movement of the peptide molecules could be determined quantitatively for the probed short-time regime. The findings could be confirmed very precisely by MD simulations. Furthermore, the article presents an estimation for the radius of influence of the peptides on the lipid long-range dynamics which could be determined by consistently combining results from experiment and simulation.
CRIS-Team WoS Importer:2020-11-27

Molecular characterization of the equine AEG1 locus. - Schambony, Alexandra; et al. (Gene, 2002)
Acidic epididymal glycoprotein 1 (AEG1), also called cysteine-rich secretory protein 1 (CRISP1), is a member of the CRISP protein family which is characterized by 16 conserved cysteine residues at the C-terminus. The CRISP proteins are expressed in the male genital tract and are thought to be involved in sperm-egg fusion. Therefore, their genes are of interest as candidate genes for inherited male fertility dysfunctions and as putative quantitative trait loci for male fertility traits. In this report, the cloning and DNA sequence of 90 kb of horse genomic DNA from equine chromosome 20q22 containing the complete equine AEG1 gene are described. The equine AEG1 gene consists of eight exons spanning 31 kb. Analysis of equine AEG1 transcripts did not reveal any evidence for alternative splicing, however three different transcription start sites are used. The first transcription start site is located 20 nt downstream of a TATA box motif. Reverse transcription polymerase chain reaction analysis demonstrated that AEG1 is expressed in different parts of the epididymis, whereas it is hardly detectable in the testis. The naturally occurring diversity of the equine AEG1 gene in different horse breeds was investigated and several polymorphisms are reported, including one that affects the amino acid sequence. Finally, sequence comparisons revealed that the intronless equine PGK2 gene for the testis-specific phosphoglycerate kinase is located approximately 39 kb downstream of AEG1.

Molecular cross-talk between Y5-receptor and neuropeptide Y drives liver cancer - Dietrich, Peter; Wormser, Laura; Fritz, Valerie; Seitz, Tatjana; de Maria, Monica; Schambony, Alexandra; Kremer, Andreas; Günther, Claudia; Itzel, Timo; Thasler, Wolfgang E.; Teufel, Andreas; Trebicka, Jonel; et al. (Journal of Clinical Investigation, 2020)
Hepatocellular carcinoma (HCC) is clearly age-related and represents one of the deadliest cancer types worldwide. Due to globally increasing risk factors including metabolic disorders, the incidence rates of HCC are still rising. However, the molecular hallmarks of HCC remain poorly understood. Neuropeptide Y (NPY) and NPY-receptors represent a highly conserved, stress-activated system which is involved in diverse cancer-related hallmarks including aging and metabolic alterations, but its impact on liver cancer had been unclear. Here, we observed increased NPY5-receptor (Y5R) expression in HCC which correlated with tumor growth and survival. Furthermore, we found that its ligand NPY was secreted by peri-tumorous hepatocytes. Hepatocyte-derived NPY promoted HCC progression by Y5R-activation. Transforming growth factor beta 1 (TGFβ1) was identified as a regulator of NPY in hepatocytes and induced Y5R in invasive cancer cells. Moreover, NPY-conversion by dipeptidylpeptidase 4 (DPP4) augmented Y5R-activation and function in liver cancer. The TGFβ-NPY-Y5R-axis and DPP4 represent attractive therapeutic targets for controlling liver cancer progression.
EVALuna2:212290
Keywords: Aging; Cancer; Hepatology

Molecular Mechanisms of Wnt Pathway Specificity - Schambony, Alexandra; Zaman, Guido J.R.; Verkaar, Folkert (Wnt Signaling in Development and Disease, 2014)

Negative regulation of Wnt signaling mediated by CK1-phosphorylated Dishevelled via Ror2. - Witte, Florian; Bernatik, Ondrej; Kirchner, Katharina; Masek, Jan; Mahl, Annika; Krejci, Pavel; Mundlos, Stefan; Schambony, Alexandra; Bryja, Vitezslav; Stricker, Sigmar (The FASEB Journal, 2010)
Dishevelled (Dvl) is a multifunctional effector of different Wnt cascades. Both canonical Wnt3a and noncanonical Wnt5a stimulate casein-kinase-1 (CK1) -mediated phosphorylation of Dvl, visualized as electrophoretic mobility shift [phosphorylated and shifted Dvl (ps-Dvl)]. However, the role of this phosphorylation remains obscure. Here we report the functional interaction of ps-Dvl with the receptor tyrosine kinase Ror2, which is an alternative Wnt receptor and is able to inhibit canonical Wnt signaling. We demonstrate interaction between Ror2 and ps-Dvl at the cell membrane after Wnt3a or Wnt5a stimulus dependent on CK1. Ps-Dvl interacts with the C-terminal proline-serine-threonine-rich domain of Ror2, which is required for efficient inhibition of canonical Wnt signaling. We further show that the Dvl C terminus, which seems to be exposed in ps-Dvl and efficiently binds Ror2, is an intrinsic negative regulator of the canonical Wnt pathway downstream of beta-catenin. The Dvl C terminus is necessary and sufficient to inhibit canonical Wnt/beta-catenin signaling, which is dependent on the presence of Ror2. Furthermore, both the Dvl C terminus and CK1epsilon can inhibit the Wnt5a/Ror2/ATF2 pathway in mammalian cells and Xenopus explant cultures. This suggests that phosphorylation of Dvl triggers negative feedback regulation for different branches of Wnt signaling in a Ror2-dependent manner.

Noncanonical WNT5A controls the activation of latent TGF-β to drive fibroblast activation and tissue fibrosis - Trinh-Minh, Thuong; Chen, Chih-Wei; Tran-Manh, Cuong; Li, Yi Nan; Zhu, Honglin; Zhou, Xiang; Chakraborty, Debomita; Zhang, Yun; Rauber, Simon; Dees, Clara; Lin, Neng-Yu; Kah, Delf-Thorge Eric; et al. (Journal of Clinical Investigation, 2024)
Transforming growth factor β (TGF-β) signaling is a core pathway of fibrosis, but the molecular regulation of the activation of latent TGF-β remains incompletely understood. Here, we demonstrate a crucial role of WNT5A/JNK/ROCK signaling that rapidly coordinates the activation of latent TGF-β in fibrotic diseases. WNT5A was identified as a predominant noncanonical WNT ligand in fibrotic diseases such as systemic sclerosis, sclerodermatous chronic graft-versus-host disease, and idiopathic pulmonary fibrosis, stimulating fibroblast-to-myofibroblast transition and tissue fibrosis by activation of latent TGF-β. The activation of latent TGF-β requires rapid JNK- and ROCK-dependent cytoskeletal rearrangements and integrin αV (ITGAV). Conditional ablation of WNT5A or its downstream targets prevented activation of latent TGF-β, rebalanced TGF-β signaling, and ameliorated experimental fibrosis. We thus uncovered what we believe to be a novel mechanism for the aberrant activation of latent TGF-β in fibrotic diseases and provided evidence for targeting WNT5A/JNK/ROCK signaling in fibrotic diseases as a new therapeutic approach.
CRIS-Team Scopus Importer:2024-05-24
Keywords: Dermatology; Fibrosis; Pulmonology

PAPC and the Wnt5a/Ror2 pathway control the invagination of the otic placode in Xenopus. - Jung, Barbara; Koehler, Almut; Schambony, Alexandra; Wedlich, Doris (Bmc Developmental Biology, 2011)
BACKGROUND:Paraxial protocadherin (PAPC) plays a crucial role in morphogenetic movements during gastrulation and somitogenesis in mouse, zebrafish and Xenopus. PAPC influences cell-cell adhesion mediated by C-Cadherin. A putative direct adhesion activity of PAPC is discussed. PAPC also promotes cell elongation, tissue separation and coordinates cell mass movements. In these processes the signaling function of PAPC in activating RhoA/JNK and supporting Wnt-11/PCP by binding to frizzled 7 (fz7) is important.RESULTS:Here we demonstrate by loss of function experiments in Xenopus embryos that PAPC regulates another type of morphogenetic movement, the invagination of the ear placode. Knockdown of PAPC by antisense morpholinos results in deformation of the otic vesicle without altering otocyst marker expression. Depletion of PAPC could be rescued by full-length PAPC, constitutive active RhoA and by the closely related PCNS but not by classical cadherins. Also the cytoplasmic deletion mutant M-PAPC, which influences cell adhesion, does not rescue the PAPC knockdown. Interestingly, depletion of Wnt5a or Ror2 which are also expressed in the otocyst phenocopies the PAPC morphant phenotype.CONCLUSIONS:PAPC signaling via RhoA and Wnt5a/Ror2 activity are required to keep cells aligned in apical-basal orientation during invagination of the ear placode. Since neither the cytoplasmic deletion mutant M-PAPC nor a classical cadherin is able to rescue loss of PAPC we suggest that the signaling function of the protocadherin rather than its role as modulator of cell-cell adhesion is required during invagination of the ear placode.

Paraxial protocadherin coordinates cell polarity during convergent extension via Rho A and JNK. - Unterseher, Frank; Hefele, Jörg; Giehl, Klaudia; De Robertis, E.M.; Wedlich, Doris; Schambony, Alexandra (EMBO Journal, 2004)
Convergent extension movements occur ubiquitously in animal development. This special type of cell movement is controlled by the Wnt/planar cell polarity (PCP) pathway. Here we show that Xenopus paraxial protocadherin (XPAPC) functionally interacts with the Wnt/PCP pathway in the control of convergence and extension (CE) movements in Xenopus laevis. XPAPC functions as a signalling molecule that coordinates cell polarity of the involuting mesoderm in mediolateral orientation and thus selectively promotes convergence in CE movements. XPAPC signals through the small GTPases Rho A and Rac 1 and c-jun N-terminal kinase (JNK). Loss of XPAPC function blocks Rho A-mediated JNK activation. Despite common downstream components, XPAPC and Wnt/PCP signalling are not redundant, and the activity of both, XPAPC and PCP signalling, is required to coordinate CE movements.

Pgam5 released from damaged mitochondria induces mitochondrial biogenesis via Wnt signaling - Bernkopf, Dominic; Jalal, Kowcee; Brückner, Martina; Knaup, Karl; Gentzel, Marc; Schambony, Alexandra; Behrens, Jürgen (The Journal of Cell Biology, 2018)
Mitochondrial abundance is dynamically regulated and was previously shown to be increased by Wnt/β-catenin signaling. Pgam5 is a mitochondrial phosphatase which is cleaved by the rhomboid protease presenilin-associated rhomboid-like protein (PARL) and released from membranes after mitochondrial stress. In this study, we show that Pgam5 interacts with the Wnt pathway component axin in the cytosol, blocks axin-mediated β-catenin degradation, and increases β-catenin levels and β-catenin-dependent transcription. Pgam5 stabilized β-catenin by inducing its dephosphorylation in an axin-dependent manner. Mitochondrial stress triggered by carbonyl cyanide m-chlorophenyl hydrazone (CCCP) treatment led to cytosolic release of endogenous Pgam5 and subsequent dephosphorylation of β-catenin, which was strongly diminished in Pgam5 and PARL knockout cells. Similarly, hypoxic stress generated cytosolic Pgam5 and led to stabilization of β-catenin, which was abolished by Pgam5 knockout. Cells stably expressing cytosolic Pgam5 exhibit elevated β-catenin levels and increased mitochondrial numbers. Our study reveals a novel mechanism by which damaged mitochondria might induce replenishment of the mitochondrial pool by cell-intrinsic activation of Wnt signaling via the Pgam5-β-catenin axis.
EVALuna2:34942

Preferential expression of cystein-rich secretory protein-3 (CRISP-3) in chronic pancreatitis. - Schambony, Alexandra; et al. (Histology and Histopathology, 2003)
BACKGROUND:Chronic pancreatitis (CP) is a progressive inflammatory process resulting in exocrine and endocrine pancreatic insufficiency in advanced stages. Cysteine-rich secretory protein (CRISP-3) has been identified as a defense-associated molecule with predominant expression in the salivary gland, pancreas and prostate.AIMS:In this study, we investigated CRISP-3 expression in normal pancreatic tissues, chronic pancreatitis tissues, pancreatic cancer tissues and pancreatic cancer cell lines, as well as in other gastrointestinal organs.MATERIALS AND METHODS:15 normal pancreatic tissues, 14 chronic pancreatitis tissues and 14 pancreatic cancer tissues as well as three pancreatic cancer cell lines were analyzed. Moreover, hepatocellular carcinoma and esophageal, stomach and colon cancers were also analyzed together with the corresponding normal controls.RESULTS:CRISP-3 was expressed at moderate to high levels in chronic pancreatitis tissues and at moderate levels in pancreatic cancer tissues but at low levels in normal pancreatic tissues, and was absent in three pancreatic cancer cell lines. CRISP-3 expression was below the level of detection in all cancerous gastrointestinal tissues and in all normal tissues except 2 of 16 colon tissue samples. CRISP-3 mRNA signals and immunoreactivity were strongly present in the cytoplasm of degenerating acinar cells and in small proliferating ductal cells in CP tissues and CP-like lesions in pancreatic cancer tissues. In contrast, CRISP-3 expression was weak to absent in the cytoplasm of cancer cells as well as in acinar cells and ductal cells in pancreatic cancer tissues and normal pancreatic tissues.CONCLUSION:These results reveal that the distribution of CRISP-3 in gastrointestinal tissues is predominantly in the pancreas. High levels of CRISP-3 in acinar cells dedifferentiating into small proliferating ductal cells in CP and CP-like lesions in pancreatic cancer suggests a role of this molecule in the pathophysiology of CP.

Prohibitin1 acts as a neural crest specifier in Xenopus development by repressing the transcription factor E2F1 - Schneider, Martina; Schambony, Alexandra; Wedlich, Doris (Development, 2010)
Prohibitin 1 (phb1), which was initially described as an inhibitor of cell proliferation, is a highly conserved protein found in multiple cellular compartments. In the nucleus it interacts with the transcriptional regulators Rb and E2F1 and controls cell proliferation and apoptosis. Here we unravel an unexpected novel function for phb1 in Xenopus cranial neural crest (CNC) development. Xphb1 is maternally expressed; zygotically expressed neurula stage transcripts accumulate in the CNC and the neural tube. Knockdown of Xphb1 by antisense morpholino injection results in the loss of foxD3, snail2 and twist expression, whereas expression of c-myc, AP-2 and snail1 remains unaffected. Xphb2, its closest relative, cannot substitute for Xphb1, underlining the specificity of Xphb1 function. Epistatic analyses place Xphb1 downstream of c-myc and upstream of foxD3, snail2 and twist. To elucidate which subdomain in Xphb1 is required for neural crest gene regulation we generated deletion mutants and tested their rescue ability in Xphb1 morphants. The E2F1-binding domain was found to be necessary for Xphb1 function in neural crest development. Gain- and loss-of-function experiments reveal that Xphb1 represses E2F1 activity; suppression of E2F1 through Xphb1 is required for twist, snail2 and foxD3 expression in the CNC. With the Xphb1 dependency of a subset of CNC specifiers downstream of c-myc, we have identified a new branching point in the neural crest gene regulatory network.
Keywords: c-myc; Cranial neural crest; Snail/slug regulation; Xenopus

Ror2 signaling is required for local upregulation of GFD6 and activation of BMP signaling at the neural plate border - Schille, Carolin; Bayerlova, Michaela; Bleckmann, Annalen; Schambony, Alexandra (Development, 2016)
The receptor tyrosine kinase Ror2 is a major Wnt receptor that activates β-catenin-independent signaling and plays a conserved role in the regulation of convergent extension movements and planar cell polarity in vertebrates. Mutations in the ROR2 gene cause recessive Robinow syndrome in humans, a short-limbed dwarfism associated with craniofacial malformations. Here, we show that Ror2 is required for local upregulation of gdf6 at the neural plate border in Xenopus embryos. Ror2 morphant embryos fail to upregulate neural plate border genes and show defects in the induction of neural crest cell fate. These embryos lack the spatially restricted activation of BMP signaling at the neural plate border at early neurula stages, which is required for neural crest induction. Ror2-dependent planar cell polarity signaling is required in the dorsolateral marginal zone during gastrulation indirectly to upregulate the BMP ligand Gdf6 at the neural plate border and Gdf6 is sufficient to rescue neural plate border specification in Ror2 morphant embryos. Thereby, Ror2 links Wnt/planar cell polarity signaling to BMP signaling in neural plate border specification and neural crest induction.
Keywords: BMP; Gdf6; Neural crest; Neural plate border; Ror2; Wnt

ROR-Family Receptor Tyrosine Kinases. - Stricker, Sigmar; Rauschenberger, Verena; Schambony, Alexandra (Current Topics in Developmental Biology, 2017)
ROR-family receptor tyrosine kinases form a small subfamily of receptor tyrosine kinases (RTKs), characterized by a conserved, unique domain architecture. ROR RTKs are evolutionary conserved throughout the animal kingdom and act as alternative receptors and coreceptors of WNT ligands. The intracellular signaling cascades activated downstream of ROR receptors are diverse, including but not limited to ROR-Frizzled-mediated activation of planar cell polarity signaling, RTK-like signaling, and antagonistic regulation of WNT/β-Catenin signaling. In line with their diverse repertoire of signaling functions, ROR receptors are involved in the regulation of multiple processes in embryonic development such as development of the axial and paraxial mesoderm, the nervous system and the neural crest, the axial and appendicular skeleton, and the kidney. In humans, mutations in the ROR2 gene cause two distinct developmental syndromes, recessive Robinow syndrome (RRS; MIM 268310) and dominant brachydactyly type B1 (BDB1; MIM 113000). In Robinow syndrome patients and animal models, the development of multiple organs is affected, whereas BDB1 results only in shortening of the distal phalanges of fingers and toes, reflecting the diversity of functions and signaling activities of ROR-family RTKs. In this chapter, we give an overview on ROR receptor structure and function. We discuss their signaling functions and role in vertebrate embryonic development with a focus on those developmental processes that are affected by mutations in the ROR2 gene in human patients.

Signaling pathways and tissue interactions in neural plate border formation - Schille, Carolin; Schambony, Alexandra (Neurogenesis, 2017)
The neural crest is a transient cell population that gives rise to various cell types of multiple tissues and organs in the vertebrate embryo. Neural crest cells arise from the neural plate border, a region localized at the lateral borders of the prospective neural plate. Temporally and spatially coordinated interaction with the adjacent tissues, the non-neural ectoderm, the neural plate and the prospective dorsolateral mesoderm, is required for neural plate border specification. Signaling molecules, namely BMP, Wnt and FGF ligands and corresponding antagonists are derived from these tissues and interact to induce the expression of neural plate border specific genes. The present mini-review focuses on the current understanding of how the NPB territory is formed and accentuates the need for coordinated interaction of BMP and Wnt signaling pathways and precise tissue communication that are required for the definition of the prospective NC in the competent ectoderm.
Keywords: BMP; GDF6; neural crest; Neural plate border; neurocristophathies; Recessive Robinow Syndrome; Ror2; Wnt

Structural and functional characterization of the Wnt inhibitor APC membrane recruitment 1 (Amer1). - Tanneberger, Kristina; Pfister, Astrid; Kriz, Vitezslav; Bryja, Vitezslav; Schambony, Alexandra; Behrens, Jürgen (Journal of Biological Chemistry, 2011)
Amer1/WTX binds to the tumor suppressor adenomatous polyposis coli and acts as an inhibitor of Wnt signaling by inducing β-catenin degradation. We show here that Amer1 directly interacts with the armadillo repeats of β-catenin via a domain consisting of repeated arginine-glutamic acid-alanine (REA) motifs, and that Amer1 assembles the β-catenin destruction complex at the plasma membrane by recruiting β-catenin, adenomatous polyposis coli, and Axin/Conductin. Deletion or specific mutations of the membrane binding domain of Amer1 abolish its membrane localization and abrogate negative control of Wnt signaling, which can be restored by artificial targeting of Amer1 to the plasma membrane. In line, a natural splice variant of Amer1 lacking the plasma membrane localization domain is deficient for Wnt inhibition. Knockdown of Amer1 leads to the activation of Wnt target genes, preferentially in dense compared with sparse cell cultures, suggesting that Amer1 function is regulated by cell contacts. Amer1 stabilizes Axin and counteracts Wnt-induced degradation of Axin, which requires membrane localization of Amer1. The data suggest that Amer1 exerts its negative regulatory role in Wnt signaling by acting as a scaffold protein for the β-catenin destruction complex and promoting stabilization of Axin at the plasma membrane.

The extracellular domain of Lrp5/6 inhibits noncanonical Wnt signaling in vivo. - Bryja, Vitezslav; Andersson, Emma R.; Schambony, Alexandra; Esner, Milan; Bryjova, Lenka; Biris, Kristin K.; Hall, Anita C.; Kraft, Bianca; Cajanek, Lukas; Yamaguchi, Terry P.; Buckingham, Margaret; Arenas, Ernest (Molecular Biology of the Cell, 2009)
Lrp5/6 are crucial coreceptors for Wnt/beta-catenin signaling, a pathway biochemically distinct from noncanonical Wnt signaling pathways. Here, we examined the possible participation of Lrp5/6 in noncanonical Wnt signaling. We found that Lrp6 physically interacts with Wnt5a, but that this does not lead to phosphorylation of Lrp6 or activation of the Wnt/beta-catenin pathway. Overexpression of Lrp6 blocks activation of the Wnt5a downstream target Rac1, and this effect is dependent on intact Lrp6 extracellular domains. These results suggested that the extracellular domain of Lrp6 inhibits noncanonical Wnt signaling in vitro. In vivo, Lrp6-/- mice exhibited exencephaly and a heart phenotype. Surprisingly, these defects were rescued by deletion of Wnt5a, indicating that the phenotypes resulted from noncanonical Wnt gain-of-function. Similarly, Lrp5 and Lrp6 antisense morpholino-treated Xenopus embryos exhibited convergent extension and heart phenotypes that were rescued by knockdown of noncanonical XWnt5a and XWnt11. Thus, we provide evidence that the extracellular domains of Lrp5/6 behave as physiologically relevant inhibitors of noncanonical Wnt signaling during Xenopus and mouse development in vivo.

The function of the two-pore channel TPC1 depends on dimerization of its carboxy-terminal helix. - Larisch, Nina; Kirsch, Sonja; Schambony, Alexandra; Studtrucker, Tanja; Böckmann, Rainer; Dietrich, Petra (Cellular and Molecular Life Sciences, 2016)
Two-pore channels (TPCs) constitute a family of intracellular cation channels with diverse permeation properties and functions in animals and plants. In the model plant Arabidopsis, the vacuolar cation channel TPC1 is involved in propagation of calcium waves and in cation homeostasis. Here, we discovered that the dimerization of a predicted helix within the carboxyl-terminus (CTH) is essential for the activity of TPC1. Bimolecular fluorescence complementation and co-immunoprecipitation demonstrated the interaction of the two C-termini and pointed towards the involvement of the CTH in this process. Synthetic CTH peptides dimerized with a dissociation constant of 3.9 µM. Disruption of this domain in TPC1 either by deletion or point mutations impeded the dimerization and cation transport. The homo-dimerization of the CTH was analyzed in silico using coarse-grained molecular dynamics (MD) simulations for the study of aggregation, followed by atomistic MD simulations. The simulations revealed that the helical region of the wild type, but not a mutated CTH forms a highly stable, antiparallel dimer with characteristics of a coiled-coil. We propose that the voltage- and Ca(2+)-sensitive conformation of TPC1 depends on C-terminal dimerization, adding an additional layer to the complex regulation of two-pore cation channels.

The LIM domain protein Wtip interacts with the receptor tyrosine kinase Ror2 and inhibits canonical Wnt signalling. - Van Wijk, Nicole Verhey; Witte, Florian; Feike, Ann Carolin; Schambony, Alexandra; Birchmeier, Walter; Mundlos, Stefan; Stricker, Sigmar (Biochemical and Biophysical Research Communications, 2009)
Wtip is a LIM domain protein of the Ajuba/Zyxin family involved in kidney and neural crest development; Ror2 is a receptor tyrosine kinase involved in the development of skeleton, heart, lung, genitalia and kidneys. Here we describe Wtip as an intracellular interaction partner of Ror2. Full-length Ror2 recruits Wtip to the cell membrane, a mutant involved in human disease fails to do so. Both genes and proteins show overlapping expression in the mouse embryo. We show that Wtip is able to inhibit canonical Wnt signalling in mammalian cells and in Xenopus embryos linking Wtip to a crucial developmental pathway.

The phosphatase Pgam5 antagonizes Wnt/β-catenin signaling in embryonic anterior-posterior axis patterning - Rauschenberger, Verena; Bernkopf, Dominic; Krenn, Sabrina; Jalal, Kowcee; Heller, Jens; Behrens, Jürgen; Gentzel, Marc; Schambony, Alexandra (Development, 2017)
Keywords: Anteriorposterior patterning; Dvl2; Pgam5; Phosphatase; Wnt; Xenopus

The role of seminal plasma in fertilisation - Schambony, Alexandra; et al. (Tieraerztliche Umschau, 1998)
... The role of seminal plasma in fertilisation. Topfer-Petersen, E, Waberski, D, Hess, O, Bellair, S, Schambony , A , Ekhlasi-Hundrieser, M, Gentzel, M and Reineke, A (1998) The role of seminal plasma in fertilisation. Tieraerztliche Umschau, 53 7: 447-454. Document type: Journal

Waif1/5T4 inhibits Wnt/β-catenin signaling and activates noncanonical Wnt pathways by modifying LRP6 subcellular localization. - Kagermeier-Schenk, Birgit; Wehner, Daniel; Oezhan-Kizil, Guenes; Yamamoto, Hideki; Li, Jian; Kirchner, Katharina; Hoffmann, Christian; Stern, Peter; Kikuchi, Akira; Schambony, Alexandra; Weidinger, Gilbert (Developmental Cell, 2011)
Wnt proteins can activate distinct signaling pathways, but little is known about the mechanisms regulating pathway selection. Here we show that the metastasis-associated transmembrane protein Wnt-activated inhibitory factor 1 (Waif1/5T4) interferes with Wnt/β-catenin signaling and concomitantly activates noncanonical Wnt pathways. Waif1 inhibits β-catenin signaling in zebrafish and Xenopus embryos as well as in mammalian cells, and zebrafish waif1a acts as a direct feedback inhibitor of wnt8-mediated mesoderm and neuroectoderm patterning during zebrafish gastrulation. Waif1a binds to the Wnt coreceptor LRP6 and inhibits Wnt-induced LRP6 internalization into endocytic vesicles, a process that is required for pathway activation. Thus, Waif1a modifies Wnt/β-catenin signaling by regulating LRP6 subcellular localization. In addition, Waif1a enhances β-catenin-independent Wnt signaling in zebrafish embryos and Xenopus explants by promoting a noncanonical function of Dickkopf1. These results suggest that Waif1 modulates pathway selection in Wnt-receiving cells.

WNT5A PROMOTES FIBROBLAST ACTIVATION AND TISSUE FIBROSIS BY ROR2/RYK DEPENDENT ACTIVATION OF PCP-SIGNALING - Chen, Chih-Wei; Lin, N. -Y.; Zhang, Yun; Huang, J.; Palumbo-Zerr, K.; Schambony, Alexandra; Beyer, Christian; Schett, Georg; Distler, Jörg (2016)
EVALuna2:13488

Wnt5a/Ror2-induced upregulation of xPAPC requires xShcA. - Feike, Ann Caroline; Rachor, Klara; Gentzel, Marc; Schambony, Alexandra (Biochemical and Biophysical Research Communications, 2010)
Ror receptor-tyrosine kinases act as Wnt-5a receptors in beta-catenin independent Wnt-signaling pathways. In Xenopus, expression of xPAPC is regulated by a Wnt-5a/Ror2 pathway, which resembles typical signaling cascades downstream of receptor-tyrosine kinases. Here, we have identified the phospho-tyrosine binding protein ShcA as an intracellular binding partner of Ror2. ShcA binds to a conserved motif in Ror2 via its SH2-domain. Wnt-5a induces clustering of Ror2 in the cell membrane and recruitment of ShcA to the Ror2 receptor complex. We further show that ShcA is co-expressed with Ror2 in developing Xenopus embryos and ShcA is required for Wnt-5a/Ror2 mediated upregulation of xPAPC, demonstrating the functional relevance of this interaction.

Wnt-5A/Ror2 regulate expression of XPAPC through an alternative noncanonical signaling pathway. - Schambony, Alexandra; Wedlich, Doris (Developmental Cell, 2007)
XWnt-5A, a member of the nontransforming Wnt-5A class of Wnt ligands, is required for convergent extension movements in Xenopus embryos. XWnt-5A knockdown phenocopies paraxial protocadherin (XPAPC) loss of function: involuted mesodermal cells fail to align mediolaterally, which results in aberrant movements and a selective inhibition of constriction. XWnt-5A depletion was rescued by coinjection of XPAPC RNA, indicating that XWnt-5A acts upstream of XPAPC. XWnt-5A, but not XWnt-11, stimulates XPAPC expression independent of the canonical Wnt/beta-catenin pathway. We show that transcriptional regulation of XPAPC by XWnt-5A requires the receptor tyrosine kinase Ror2. XWnt-5A/Xror2 signal through PI3 kinase and cdc42 to activate the JNK signaling cascade with the transcription factors ATF2 and c-jun. The Wnt-5A/Ror2 pathway represents an alternative, distinct branch of noncanonical Wnt signaling that controls gene expression and is required in the regulation of convergent extension movements in Xenopus gastrulation.

Wnt Signaling and Cell Migration - Schambony, Alexandra; Wedlich, Doris (Wnt Signaling in Development, 2003)
The significance of Wnt signaling for cell migration came into play most recently, and with it, a burst displaying the diversity of Wnt family members in signal transduction and physiological function. Our most comprehensive knowledge of how Wnt signaling controls

Wnt/β-catenin signaling requires interaction of the Dishevelled DEP domain and C terminus with a discontinuous motif in Frizzled. - Tauriello, Daniele V. F.; Jordens, Ingrid; Kirchner, Katharina; Slootstra, Jerry W.; Kruitwagen, Tom; Bouwman, Britta A. M.; Noutsou, Maria; Rudiger, Stefan G. D.; Schwamborn, Klaus; Schambony, Alexandra; Maurice, Madelon M. (Proceedings of the National Academy of Sciences of the United States of America, 2012)
Wnt binding to members of the seven-span transmembrane Frizzled (Fz) receptor family controls essential cell fate decisions and tissue polarity during development and in adulthood. The Fz-mediated membrane recruitment of the cytoplasmic effector Dishevelled (Dvl) is a critical step in Wnt/β-catenin signaling initiation, but how Fz and Dvl act together to drive downstream signaling events remains largely undefined. Here, we use an Fz peptide-based microarray to uncover a mechanistically important role of the bipartite Dvl DEP domain and C terminal region (DEP-C) in binding a three-segmented discontinuous motif in Fz. We show that cooperative use of two conserved motifs in the third intracellular loop and the classic C-terminal motif of Fz is required for DEP-C binding and Wnt-induced β-catenin activation in cultured cells and Xenopus embryos. Within the complex, the Dvl DEP domain mainly binds the Fz C-terminal tail, whereas a short region at the Dvl C-terminal end is required to bind the Fz third loop and stabilize the Fz-Dvl interaction. We conclude that Dvl DEP-C binding to Fz is a key event in Wnt-mediated signaling relay to β-catenin. The discontinuous nature of the Fz-Dvl interface may allow for precise regulation of the interaction in the control of Wnt-dependent cellular responses.

β-Arrestin interacts with the beta/gamma subunits of trimeric G-proteins and dishevelled in the Wnt/Ca(2+) pathway in xenopus gastrulation. - Seitz, Katharina; Duersch, Verena; Harnos, Jakub; Bryja, Vitezslav; Gentzel, Marc; Schambony, Alexandra (PLoS ONE, 2014)
β-Catenin independent, non-canonical Wnt signaling pathways play a major role in the regulation of morphogenetic movements in vertebrates. The term non-canonical Wnt signaling comprises multiple, intracellularly divergent, Wnt-activated and β-Catenin independent signaling cascades including the Wnt/Planar Cell Polarity and the Wnt/Ca cascades. Wnt/Planar Cell Polarity and Wnt/Ca pathways share common effector proteins, including the Wnt ligand, Frizzled receptors and Dishevelled, with each other and with additional branches of Wnt signaling. Along with the aforementioned proteins, β-Arrestin has been identified as an essential effector protein in the Wnt/β-Catenin and the Wnt/Planar Cell Polarity pathway. Our results demonstrate that β-Arrestin is required in the Wnt/Ca signaling cascade upstream of Protein Kinase C (PKC) and Ca/ Calmodulin-dependent Protein Kinase II (CamKII). We have further characterized the role of β-Arrestin in this branch of non-canonical Wnt signaling by knock-down and rescue experiments in Xenopus embryo explants and analyzed protein-protein interactions in 293T cells. Functional interaction of β-Arrestin, the β subunit of trimeric G-proteins and Dishevelled is required to induce PKC activation and membrane translocation. In Xenopus gastrulation, β-Arrestin function in Wnt/Ca signaling is essential for convergent extension movements. We further show that β-Arrestin physically interacts with the β subunit of trimeric G-proteins and Dishevelled, and that the interaction between β-Arrestin and Dishevelled is promoted by the beta/gamma subunits of trimeric G-proteins, indicating the formation of a multiprotein signaling complex. © 2014 Seitz et al.

β-arrestins - Scaffolds and signalling elements essential for WNT/Frizzled signalling pathways? - Schulte, Gunnar; Schambony, Alexandra; Bryja, Vitezslav (British Journal of Pharmacology, 2010)
β-arrestins were originally identified as negative regulators of G protein-coupled receptor signalling. Recent studies have revealed that β-arrestins serve as intracellular scaffolds and signalling intermediates. Their diverse functions in intracellular signalling pathways provide mechanisms for achieving signal specificity that might be attacked for pharmacological intervention. Here, we summarize the importance of β-arrestin function for WNT [wingless (from Drosophila) and the oncogene int-1]/Frizzled (FZD) signalling. WNTs are secreted lipoglycoproteins that act through the seven transmembrane-spanning receptors of the FZD family. It recently became evident that β-arrestins are required for cellular communication by means of WNTs and FZDs both in cellular systems and in vivo. Although the overall importance of arrestin for WNT/FZD signalling remains obscure, interaction with the central phosphoprotein Dishevelled and the endocytic machinery implicates β-arrestin as a determinant of WNT signalling specificity, a mediator of WNT/FZD desensitization and a regulator of signalling compartmentation. © 2009 The Authors.
Keywords: β-catenin; Canonical signalling; Casein kinase; Desensitization; Dishevelled; Endocytosis; Internalization; Non-canonical signalling; ROR; RYK

β-catenin-independent WNT signaling and Ki67 in contrast to the estrogen receptor status are prognostic and associated with poor prognosis in breast cancer liver metastases. - Bleckmann, Annalen; Conradi, Lena-Christin; Menck, Kerstin; Schmick, Nadine Annette; Schubert, Antonia; Rietkoetter, Eva; Arackal, Jetcy; Middel, Peter; Schambony, Alexandra; Liersch, Torsten; Homayounfar, Kia; Beissbarth, Tim; et al. (Clinical & Experimental Metastasis, 2016)
Liver metastasis development in breast cancer patients is common and confers a poor prognosis. So far, the prognostic significance of surgical resection and clinical relevance of biomarker analysis in metastatic tissue have barely been investigated. We previously demonstrated an impact of WNT signaling in breast cancer brain metastasis. This study aimed to investigate the value of established prognostic markers and WNT signaling components in liver metastases. Overall N = 34 breast cancer liver metastases (with matched primaries in 19/34 cases) were included in this retrospective study. Primaries and metastatic samples were analyzed for their expression of the estrogen (ER) and progesterone receptor, HER-2, Ki67, and various WNT signaling-components by immunohistochemistry. Furthermore, β-catenin-dependent and -independent WNT scores were generated and analyzed for their prognostic value. Additionally, the influence of the alternative WNT receptor ROR on signaling and invasiveness was analyzed in vitro. ER positivity (HR 0.09, 95 % CI 0.01-0.56) and high Ki67 (HR 3.68, 95 % CI 1.12-12.06) in the primaries had prognostic impact. However, only Ki67 remained prognostic in the metastatic tissue (HR 2.46, 95 % CI 1.11-5.44). Additionally, the β-catenin-independent WNT score correlated with reduced overall survival only in the metastasized situation (HR 2.19, 95 % CI 1.02-4.69, p = 0.0391). This is in line with the in vitro results of the alternative WNT receptors ROR1 and ROR2, which foster invasion. In breast cancer, the value of prognostic markers established in primary tumors cannot directly be translated to metastases. Our results revealed β-catenin-independent WNT signaling to be associated with poor prognosis in patients with breast cancer liver metastasis.